2017
DOI: 10.1016/j.chiabu.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the factor structure of the Childhood Trauma Questionnaire, and cumulative effect of abuse and neglect on mental health among adolescents in conflict-affected Burundi

Abstract: The present study aimed to examine the factor structure of the Childhood Trauma Questionnaire (CTQ; Bernstein & Fink, 1998), highlight rates of abuse and neglect among Burundian adolescents, compare these rates with those found in high-income nations, and examine the cumulative effect of multiple types of abuse and neglect on depression and PTSD symptoms. Participants were 231 adolescents and youth (M=14.9, SD=1.99, 58.4% female) from five provinces of Burundi, a country in Central Africa affected by war and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 53 publications
3
19
0
1
Order By: Relevance
“…Regarding the role of family abuse in the prediction of posttraumatic stress, we identified the amount of family violence, next to general traumatic events, as a significant predictor for PTSD and depressive symptoms in the North Korean sample. This is in line with previous studies suggesting that the experience of family violence increases the risk for PTSD and other mental health problems in populations affected by political conflict and violence [5, 6, 15, 16]. Our finding supports not only earlier evidence of a dose-response relationship between trauma exposure and mental health problems in people who fled North Korea [27], but also points towards family violence as an independent risk factor associated with PTSD and depression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the role of family abuse in the prediction of posttraumatic stress, we identified the amount of family violence, next to general traumatic events, as a significant predictor for PTSD and depressive symptoms in the North Korean sample. This is in line with previous studies suggesting that the experience of family violence increases the risk for PTSD and other mental health problems in populations affected by political conflict and violence [5, 6, 15, 16]. Our finding supports not only earlier evidence of a dose-response relationship between trauma exposure and mental health problems in people who fled North Korea [27], but also points towards family violence as an independent risk factor associated with PTSD and depression.…”
Section: Discussionsupporting
confidence: 93%
“…A substantial amount of research has documented that multiple traumatic experiences increase the chances of developing Posttraumatic Stress Disorder (PTSD), which supports the presence of a dose-response effect [11]. In particular family violence has been identified as an important risk factors which contributes to a higher vulnerability for mental disorders [6, 7, 12]. Studies with children and adolescents living in insecure and violent environments have found that family violence is closely associated with a range of psychological disorders such as PTSD [7, 1316].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that it may also be related to differences in caregiving toward boys compared with girls. For instance, Berckmoes & Reis' study ( 2016 ) among parents in Bujumbura shows that parents perceive raising boys as more challenging than raising girls, and Charak et al found a higher prevalence of physical abuse among boys than girls in Burundi ( 2017 ). Differences may also result from transactional effects between caregivers and children (Sameroff & Fiese, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, our cases represent a great variety of vulnerable household categories from diverse corners of Burundi. Second, the study's focus was on present caregiving and resilience, meaning that we have limited insight into the influence of past experiences on our findings – a question that we will try to answer with a quantitative data set, which was collected among other households in Burundi as part of the same research partnership (Charak et al 2017 ). For instance, we know little about the caregiver's own history of social behavior, and although we asked questions about the caregiver's care experiences during childhood, our findings were too limited to draw conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents did not necessarily see parental neglect as intentional, but as stemming from the impossible situation parents faced. Instead of interpreting abuse and neglect as expressions of harsh parenting, [30][31][32][33] our interlocutors explained it as resulting from crisis-induced environmental strain on families and parents.…”
Section: Discussionmentioning
confidence: 96%